An Efficient Narrowband Near‐Infrared at 1040 nm Organic Photodetector Realized by Intermolecular Charge Transfer Mediated Coupling Based on a Squaraine Dye. Issue 26 (31st May 2021) - Kim, Jin Hong; Liess, Andreas; Stolte, Matthias; Krause, Ana‐Maria; Stepanenko, Vladimir; Zhong, Chuwei; Bialas, David; Spano, Frank; Würthner, Frank
Abstract: A highly sensitive short‐wave infrared (SWIR, λ > 1000 nm) organic photodiode (OPD) is described based on a well‐organized nanocrystalline bulk‐heterojunction (BHJ) active layer composed of a dicyanovinyl‐functionalized squaraine dye (SQ‐H ) donor material in combination with PC61 BM . Through thermal annealing, dipolar SQ‐H chromophores self‐assemble in a nanoscale structure with intermolecular charge transfer mediated coupling, resulting in a redshifted and narrow absorption band at 1040 nm as well as enhanced charge carrier mobility. The optimized OPD exhibits an external quantum efficiency (EQE) of 12.3% and a full‐width at half‐maximum of only 85 nm (815 cm −1 ) at 1050 nm under 0 V, which is the first efficient SWIR OPD based on J‐type aggregates. Photoplethysmography application for heart‐rate monitoring is successfully demonstrated on flexible substrates without applying reverse bias, indicating the potential of OPDs based on short‐range coupled dye aggregates for low‐power operating wearable applications. Abstract : Narrowband near‐infrared organic photodiodes are reported based on a dipolar squaraine dye. J‐type coupling in the solid state allows SQ‐H thin films to combine favorable NIR absorption at 1040 nm and charge carrier mobility. The bulk‐heterojunction with PC61 BM yields an organic photodiode with external quantum efficiency of 12.3% at 1050 nm with a full‐width half‐maximum of 85 nm under short‐circuit condition.